PIEZO1 variant implications for biological understanding and human health - Chew W. Cheng; Sophie L. Earle; Oleksandr V. Povstyan; Chloe Randall; Katie A. Smith; Marjolaine Debant; Fraser L. Macrae; Daniel G. Beech; Anna McGrane; Fiona Bartoli; Eulashini Chuntharpursat-Bon; Richard M. Cubbon; et al. (Open Biology)
The large membrane protein PIEZO1 assembles as trimers to form exceptional mechanical force-sensing ion channels of eukaryotes. When these channels are activated by force, cell membrane permeability to calcium ions and other ions increases rapidly, coupling force to cell function through ionic control. In humans and other species, PIEZO1 is both widely expressed and functional across major systems that include the cardiovascular, haematological and musculoskeletal systems, thereby serving diverse needs. In this narrative review of the scientific literature, we address what has been learned about PIEZO1 from associations of its gene variation with human characteristics. A particular physiological importance of PIEZO1 is emerging in lymphatics and thus in the control of tissue fluid homeostasis with relevance to the disease conditions of non-immune fetal hydrops and generalized lymphatic dysplasia. Other vascular relevance is seen in lower limb venous varicosities. PIEZO1 may be non-essential in red blood cells but the amplification of its function by gene variation quite selectively alters these cells, leading to haemolytic anaemia and other related disturbances that may be only mildly adverse and confer survival advantage. We speculate on what else might be learned in humans, guided by knowledge from PIEZO1 studies in mice, and describe how knowledge accumulated to date highlights new opportunities for PIEZO1 understanding and pathways to patient benefit.